Case report: A new de novo mutation of the Troponin T2 gene in a Chinese patient with dilated cardiomyopathy - Yang, Huan; Gong, Ke; Luo, Yong; Wang, Lei; Tan, Zhiping; Yao, Yao; Xie, Li (Frontiers in Cardiovascular Medicine, 2023)
Dilated cardiomyopathy (DCM) is a cardiovascular disease characterized by persistent ventricular dilatation and systolic dysfunction. DCM has a variety of causes, including myocarditis; exposure to narcotics, alcohol, or other toxins; and metabolic or endocrine disorders. Genetic factors play a dominant role in 30%–40% of DCM cases. Here, we report a case of DCM with very severe heart failure. Because of the severity of heart failure, the patient underwent heart transplantation. We speculated that the patient's DCM might be due to a mutation; hence, we performed whole-exome sequencing of the patient and their parents, which showed a de novo heterozygous mutation (NM_001001431.2c.769G>A:p.E257K) in TNNT2, which was considered pathogenic according to the ACMG pathogenicity assessment. This finding expands the genetic map of DCM and TNNT2 and will be important for future studies on the genetic and disease relationships between DCM and TNNT2.